Edukasi Manfaat Aromaterapi terhadap Insomnia pada Lansia - Lia Effi Noviri; Yuniati Yuniati (Lembaga Pengembangan Kinerja Dosen, 2025)
Sleep disorders or insomnia refer to a condition where individuals struggle to achieve adequate sleep in terms of both quality and quantity. Insomnia sufferers often experience fatigue and drowsiness throughout the day due to a lack of optimal rest. Based on its duration, insomnia is classified into acute insomnia, lasting less than four weeks, and chronic insomnia, which persists for more than four weeks. One non-pharmacological approach to managing this issue is relaxation therapy, including the use of aromatherapy, which promotes a calming effect through pleasant scents. This community service program aims to provide awareness about the benefits of aromatherapy in managing insomnia. The methods used include health education, discussions, and Q&A sessions with participants. The target audience consisted of 12 elderly individuals experiencing sleep disturbances. The evaluation results indicated a significant improvement in participants' knowledge after the session, with 91.7% demonstrating a good understanding, while 8.3% had a moderate understanding of aromatherapy’s benefits. These findings suggest that educating the elderly on the use of aromatherapy for insomnia management positively impacts their awareness of relaxation therapy’s role in improving sleep quality. It is hoped that this method can be continuously promoted as an effective natural alternative to address sleep disorders.